Strategi Manajemen Kredit dalam Rangka Mengurangi Kredit Bermasalah di PT. BPR Ambulu Dhanaartha Kabupaten Jember - I’in Nur Khotimah; Putri Kamilatul Rohmi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze credit management strategies in reducing non-performing loans (NPL) at PT. BPR Ambulu Dhanaartha in Jember Regency. This study uses a descriptive method with a qualitative approach. Data collection was carried out through direct interviews with the bank, observation, and documentation studies from various relevant sources. The results of the study indicate that PT. BPR Ambulu Dhanaartha implements credit management strategies through the stages of planning, organizing, implementing, and monitoring. The factors causing non-performing loans come from internal aspects, such as credit analysis errors, as well as external factors, such as economic conditions and disasters. The handling strategies implemented include restructuring, rescheduling, and confiscation of collateral. By implementing strict credit analysis, structured credit policies, periodic supervision, and effective collection strategies, PT. BPR Ambulu Dhanaartha is able to minimize the risk of non-performing loans and maintain its operational stability.